2023
DOI: 10.1186/s12880-023-01009-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronary computed tomography angiography study on the relationship between the Ramus Intermedius and Atherosclerosis in the bifurcation of the left main coronary artery

Abstract: Objective This study aimed to explore the relationship between the ramus intermedius (RI) and atherosclerosis in the bifurcation of the left coronary artery (LCA). Methods Screening patients who underwent CCTA from January to September 2021, 100 patients with RI (RI group) and 100 patients without RI (no-RI group) were randomly enrolled, Evaluation of RI distribution characteristics and left main coronary artery(LM),Left anterior descending branch(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…However, if RI is precisely positioned between these arteries, its effect on their proximal diameter is minimal [19]. Additionally, some data indicate that the existence of RI is associated with an increased risk of branch point atherosclerosis [10,11,12,20]. These considerations underscore the complex interplay between RI anatomy and its potential implications for coronary artery health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if RI is precisely positioned between these arteries, its effect on their proximal diameter is minimal [19]. Additionally, some data indicate that the existence of RI is associated with an increased risk of branch point atherosclerosis [10,11,12,20]. These considerations underscore the complex interplay between RI anatomy and its potential implications for coronary artery health.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that the presence of RI increases the risk of atherosclerotic plaque formation and obstructive lesions in the left main and proximal LAD [10,12]. Zhang et al demonstrated that the presence of RI is not an independent risk factor for atherosclerotic plaque formation in the LMCA bifurcation zone, but it may indirectly increase the risk of atherosclerosis in the proximal segment of the LAD [11]. Another review highlighted the association between RI and larger anterior infarctions as well as more proximal LAD lesions [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 29 ] showed that CCTA could effectively rule out in-stent restenosis in patients with a prior PCI. CCTA may also be beneficial to stratify cardiovascular risk through other measurements and anatomic variants that could predispose to the formation of atherosclerotic plaques [ 30 , 31 ].…”
Section: Diagnosis Of Left Main Diseasementioning
confidence: 99%